2016
DOI: 10.1002/jmv.24577
|View full text |Cite
|
Sign up to set email alerts
|

Different pattern of viral infections and clinical outcomes in patient with acute exacerbation of chronic obstructive pulmonary disease and chronic obstructive pulmonary disease with pneumonia

Abstract: Respiratory viruses are well-known causes of acute exacerbation of chronic obstructive pulmonary disease (AE-COPD) and also important pathogens for concomitant pneumonia in COPD (CP-COPD). However, the differences in a viral infection pattern and clinical impacts of respiratory viruses between the two groups have not been well investigated. The clinical and microbiological data from COPD patients admitted with AE-COPD (n = 281) or CP-COPD (n = 284) between January 2010 and December 2012 were reviewed. After ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 36 publications
2
37
0
Order By: Relevance
“…75 However, another retrospective cohort analysis found a lower mortality rate in exacerbations associated with respiratory viruses compared with those testing positive for bacteria either based on culture or PCR of sputum, endotracheal aspirates or bronchoalveolar lavage. 78 Different respiratory viruses may have different effects on the immune responses and thus distinct clinical outcomes, but most studies evaluate the presence of all viruses and data are scarce on the differential clinical impact of specific virus types. Occasionally, both bacteria and viruses are identified in exacerbations and their coexistence is associated with a longer length of hospital stay and a higher symptom burden.…”
Section: Respiratory Viruses and Copd Exacerbationsmentioning
confidence: 99%
“…75 However, another retrospective cohort analysis found a lower mortality rate in exacerbations associated with respiratory viruses compared with those testing positive for bacteria either based on culture or PCR of sputum, endotracheal aspirates or bronchoalveolar lavage. 78 Different respiratory viruses may have different effects on the immune responses and thus distinct clinical outcomes, but most studies evaluate the presence of all viruses and data are scarce on the differential clinical impact of specific virus types. Occasionally, both bacteria and viruses are identified in exacerbations and their coexistence is associated with a longer length of hospital stay and a higher symptom burden.…”
Section: Respiratory Viruses and Copd Exacerbationsmentioning
confidence: 99%
“…[ 13 14 ] Several studies have been undertaken to examine the impact of COPD on the clinical outcome for patients, who developed CAP, with the majority of studies showing that COPD increased mortality in patients with CAP and prolonged the hospital stay in patients who were successfully treated for CAP. [ 9 15 16 17 ] However, some other studies have shown that COPD had no relationship with patient mortality in CAP, length of stay in the hospital, as well as more frequent admission to the ICU. [ 10 13 14 18 19 20 ]…”
Section: Linical O Utcome Of mentioning
confidence: 99%
“…[ 63 ] The findings of another prospective study showed that in patients with AECOPD, viral pneumonia was more common and was these patients had an increased rate of coinfection with bacteria, especially with pneumococcal pneumonia. [ 16 ]…”
Section: Linical C Haracteristics Of mentioning
confidence: 99%
“…6,7 Since a decade, RVs are known to cause exacerbations of chronic pulmonary diseases in infants, elderly, and immunocompromised patients. 8,9 RVs have a strong impact on the morbidity and the mortality related to asthma in these populations. 10,11,12,13 Also, it has been reported that RV infections lead to worsening of chronic obstructive pulmonary disease (COPD), 14,15 and cystic fibrosis.…”
Section: Introductionmentioning
confidence: 99%